Post-Divorce Rights of Women and Children - Astuti, Putri Widi; Prastio, Tri (Faculty of Sharia, IAIN Metro, 2022)
Dissolution of a marriage due to a court decision results in several other legal consequences, including the imposition of the obligation to pay 'iddah, mut'ah, maskan, kiswah, hadhanah, and child maintenance to be borne by the husband. This paper aims to find out how when a court decision is not carried out voluntarily and find a solution so that the decision is not only a pseudo-justice but can guarantee the justice and benefits of the decision in real terms. Based on the author's analysis, it can be concluded that if the decision regarding the ex-husband's obligations is not carried out voluntarily, an application for the execution of the decision can be submitted to the Religious Court which examines the case. The request can be based on the procedural law of the general court, namely article 197 HIR or 207-208 RBg. This effort can be carried out by the ex-wife even though the results are based on the assessment of the panel of judges who examined the case.